Political influence on non-cooperative international climate policy - Wolfgang Habla; Ralph Winkler (University of Bern, Department of Economics, 2011)
We analyze non-cooperative international climate policy in a setting of political competition by national interest groups. In the first stage, countries decide whether to set up an international emission permits market, which only forms if it is supported by all countries. In the second stage, countries non-cooperatively decide on the number of tradable or non-tradable emission allowances, depending on the type of regime. In both stages, special interest groups try to sway the government in their favor. We find that (i) both the choice of regime and the level of aggregate emissions only depend on the aggregate levels of organized stakes in all countries and not on their distribution among individual interest groups, and (ii) an increase in lobbying influence by a particular lobby group may backfire by inducing a change towards the less preferred regime.
Keywords: D72; H23; H41; Q58; 330; non-cooperative climate policy; political economy; emissions trading; organization of interest groups; environmental awareness; Internationale Umweltpolitik; Internationale Zusammenarbeit; Emissionshandel; Interessenpolitik; Nationalismus; Neue politische Ökonomie